Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/cne.20466
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the spinal trigeminal nucleus to the cochlear nucleus in the rat

Abstract: The integration of information across sensory modalities enables sound to be processed in the context of position, movement, and object identity. Inputs to the granule cell domain (GCD) of the cochlear nucleus have been shown to arise from somatosensory brain stem structures, but the nature of the projection from the spinal trigeminal nucleus is unknown. In the present study, we labeled spinal trigeminal neurons projecting to the cochlear nucleus using the retrograde tracer, Fast Blue, and mapped their distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 71 publications
3
102
0
1
Order By: Relevance
“…Since the excitatory CN-commissural pathway resembles that of non-auditory (somatosensory) projection neurons (Dehmel et al 2008;Haenggeli et al 2005;Wright and Ryugo 1996;Zhou et al 2007;Zhou and Shore 2004), it is likely to have a similar modulatory function as suggested for these non-auditory projections and may be associated with DCN synaptic plasticity under normal-hearing conditions (Tzounopoulos et al 2004;Young et al 1995;Zhou et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the excitatory CN-commissural pathway resembles that of non-auditory (somatosensory) projection neurons (Dehmel et al 2008;Haenggeli et al 2005;Wright and Ryugo 1996;Zhou et al 2007;Zhou and Shore 2004), it is likely to have a similar modulatory function as suggested for these non-auditory projections and may be associated with DCN synaptic plasticity under normal-hearing conditions (Tzounopoulos et al 2004;Young et al 1995;Zhou et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…(2) The locations in the GCD, and morphology of the excitatory CN-commissural terminal endings, as well as their immunoreactivity to VGLUT2 and not to VGLUT1, resemble that of non-auditory (somatosensory) projection neurons (Haenggeli et al 2005;Wright and Ryugo 1996;Zhou et al 2007;Zhou and Shore 2004). These non-auditory pathways can indirectly modulate DCN activity via parallel fibers, which can be either excitatory or inhibitory Davis et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…What is the best explanation for such facilitation in an early response period dominated primarily by thalamocortical inputs? There is ample evidence that subcortical auditory structures such as the dorsal cochlear nucleus (DCN) (Zhou and Shore, 2004;Haenggeli et al, 2005;Shore, 2005;Shore et al, 2008), the inferior colliculus (IC) (Jain and Shore, 2006;Zhou and Shore, 2006), and the medial division of the thalamic medial geniculate nucleus (mMGN) (Poggio and Mountcastle, 1960;Blum et al, 1979;Nicolelis et al, 1991) all receive significant somatosensory inputs and show multisensory responses. Thus, these structures, in turn, may influence subcortical somatosensory structures such as the trigeminal nucleus (TN) and the thalamic ventral posterior medial nucleus (VPM).…”
Section: Discussionmentioning
confidence: 99%
“…This type of tinnitus derives from complex somatosensory-auditory interactions and cross-modal mechanisms that mainly arise from musculoskeletal anatomical regions such as the temporomandibular joint (TMJ), craniocervical junction, cervical vertebrae, and neck and shoulder muscles (NECK) [Chan and Reade, 1994;Levine et al, 2003;Abel and Levine, 2004;Tullberg and Ernberg, 2006;Björne, 2007;Bernhardt et al, 2011;Vielsmeier et al, 2012;Buergers et al, 2014]. Animal studies have shown that projections from the auditory nerve and trigeminal and dorsal column ganglia and brainstem nuclei integrate in the cochlear dorsal nucleus [Haenggeli et al, 2005;Zhan et al, 2006;Dehmel et al, 2008;Wu et al, 2014]; furthermore, nonacoustic stimulation can modulate both the firing rates and temporal response patterns to the acoustic stimulation in the inferior colliculus, which receives inputs from the dorsal cochlear nucleus and the somatosensory nuclei [Zhou and Shore, 2006].…”
Section: Introductionmentioning
confidence: 99%